Globalisation, Eden and the Myth of Original Markets - Brock, Brian (Studies in Christian ethics, 2015)
The proposal by Adam Smith that the market is a primal human reality has arguably been the most influential of the myths offered as a substitute for the authoritative story of Eden by the Enlightenment’s founding fathers. This essay examines how rival primal stories shape agents’ moral stances by directing attention, framing conceptual priorities and in situating stated and unstated analytical presuppositions in contemporary economic discourses. Contemporary scholars have recently emphasised that the root metaphor of Smith’s economic theory is original barter. Tracing this scholarship, I will show how this picture of the human economic agent grounds the central tenets of the emerging global economic order. This vision will, however, then be shown to contrast with both the biblical vision of human economic activity (Genesis 2), medieval and reformation theological appropriations of this vision, and the political and economic institutions that pre-modern Christendom developed to express their belief in a human responsibility to serve the divine sustenance of the human race. I will conclude by suggesting why the transition from Christendom to modern global capitalism demands a deeper than usual theological analysis of phenomena we usually refer to under the heading of globalisation, calling for reformulations of basic Christian and non-Christian presumptions about economic practice and ethics.